2013
DOI: 10.1073/pnas.1312012110
|View full text |Cite
|
Sign up to set email alerts
|

Protease homolog BepA (YfgC) promotes assembly and degradation of β-barrel membrane proteins in Escherichia coli

Abstract: Gram-negative bacteria are equipped with quality-control systems for the outer membrane (OM) that sense and cope with defective biogenesis of its components. Accumulation of misfolded outer membrane proteins (OMPs) in Escherichia coli leads to activation of σ E , an essential alternative σ factor that up-regulates transcription of multiple genes required to preserve OM structure and function. Disruption of bepA (formerly yfgC), a σ E -regulated gene encoding a putative periplasmic metalloprotease, sensitizes c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
135
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(153 citation statements)
references
References 52 publications
18
135
0
Order By: Relevance
“…Most of the sensitive mutants corresponded to genes already known to be involved in envelope assembly, such as mutants defective in LPS biosynthesis (rfaC, rfaD, rfaE, rfaF, rfaH, rfaI, and rfaP mutants) or in ␤-barrel insertion at the OM (surA, bamB, and bamE mutants), which validated our experimental approach (20,21). Four mutants lacked proteins of unknown function (yciM, yfgC, yraP, and ybiX mutants) although recently YfgC has been implicated in the degradation of misfolded ␤-barrel proteins at the OM (22). We tested the sensitivity of these four mutants to other hydrophobic antibiotics and found that strains lacking yciM were the most sensitive (see Table S4), which prompted us to investigate the properties of the yciM mutant and to characterize the corresponding protein.…”
Section: Resultssupporting
confidence: 61%
“…Most of the sensitive mutants corresponded to genes already known to be involved in envelope assembly, such as mutants defective in LPS biosynthesis (rfaC, rfaD, rfaE, rfaF, rfaH, rfaI, and rfaP mutants) or in ␤-barrel insertion at the OM (surA, bamB, and bamE mutants), which validated our experimental approach (20,21). Four mutants lacked proteins of unknown function (yciM, yfgC, yraP, and ybiX mutants) although recently YfgC has been implicated in the degradation of misfolded ␤-barrel proteins at the OM (22). We tested the sensitivity of these four mutants to other hydrophobic antibiotics and found that strains lacking yciM were the most sensitive (see Table S4), which prompted us to investigate the properties of the yciM mutant and to characterize the corresponding protein.…”
Section: Resultssupporting
confidence: 61%
“…For example, the metalloprotease BepA and the disulfide isomerase DsbC have also been implicated in LptD biogenesis and disulfide rearrangement 86, 87 . BepA degrades misfolded LptD and its proposed chaperone function stimulates disulfide rearrangement in LptD through an unknown mechanism 87 . Overexpression of a variant of DsbC that traps substrates has shown that this variant interacts with LptD 86 .…”
Section: Regulation Of Lpt Bridge Formationmentioning
confidence: 99%
“…However, the biological significance of the DsbC-LptD interaction is unclear because deletion of dsbC has no detectable effect on the formation of properly oxidized LptD. Furthermore, disulfide-bond rearrangement intermediates of LptD have been shown to interact with DsbA, instead of DsbC 82, 83, 87 .…”
Section: Regulation Of Lpt Bridge Formationmentioning
confidence: 99%
“…Proper interaction of LptC with LptB 2 FG is necessary for LptA recruitment (22). Interaction of the N-terminal domain of LptD with LptA requires the correct maturation of the LptDE complex that in turns depends on nonconsecutive disulfide bond formation in LptD (16); LptE and the chaperone/protease BepA have been implicated in this process (23). Based on in vivo photo-cross-linking experiments, LPS molecules appear to cross the periplasm inside the ␤ jellyroll of LptC and LptA (9).…”
mentioning
confidence: 99%